Loneliness and Back Pain - Suksmi Yitnamurti; Agustina Konginan (Faculty of Medicine, Universitas Airlangga, 2024)
Introduction: Back pain is a common reason for being absent from work and seeking medical treatment. It can result from injury, activity, and some medical conditions. Back pain consists of lower back pain and upper back pain. Back pain does have a physical cause, but it can also be triggered by precipitating factors, namely loneliness. To explain the mechanism that associates back pain with loneliness. Methods: Literature review. Results: Loneliness is divided into 2 types, namely social loneliness and emotional loneliness. Social loneliness is associated with the absence of a social network from the same circle, with which they can share the same activities or interests. Emotional loneliness can arise due to the absence of close emotional attachment. Whether or not back pain persists depends on whether the individual chooses problem-solving or problem avoidance. Loneliness in several studies increases the morbidity rate of physical and mental illness and also the mortality rate. Early detection of somatic symptoms and loneliness requires a self-measurement scale. Therapeutic interventions aimed at increasing social connection hold merit in reducing the impact of pain on engagement with activities. The treatments are usually Cognitive Behavioral Therapy (CBT) and Antidepressants. If necessary, consulting a psychiatrist is recommended. The cooperation of orthopedists, rheumatologists, and physical therapists with psychiatrists can be useful in improving the condition of patients. Conclusions: Recommendations for management are needed both in terms of general and specific strategies, as well as loneliness interventions. Keywords: Loneliness, Back Pain, Good Health and Wellbeing